Оценка трансформаторов и их серий с использованием функциональных зависимостей параметров от обобщенного линейного размера - Загирняк, М.В.; Прус, В.В.; Невзлин, Б.И. (Електротехніка і електромеханіка, 2012)
Dependences of transformer main parameters on the generalized linear size have been revealed. Comparison criteria for transformers and their series have been formulated. Comparative estimation of transformers made by famous manufacturers has been carried out. Recommendations for transformer parameter improvement have been worked out.